Прикарпаття в історико-краєзнавчих студіях Ісидора Шараневича - Борчук, С.; Бурачок, Л.; Лизень, Є. (Краєзнавство, 2024)
Статтю присвячено одному із відомих істориків та культурно-політичних діячів ХІХ ст. – Ісидорові Івановичу Шараневичу. Мета дослідження полягає у тому, щоб на основі багатого фактичного матеріалу проаналізувати здобутки І. Шараневича в царині історико-краєзнавчих студій, висвітлити погляди дослідника, розкрити його значення в тогочасному науковому житті України, а також окреслити роль студій І. Шараневича в сучасній історичній науці. Методологічною основою є принципи об’єктивності, історизму, науковості та персоніфікації подій. У процесі написання статті було використано методи аналізу, синтезу, узагальнення, а також ретроспективний, хронологічний, просопографічний і порівняльно-історичний. Краєзнавство на Прикарпатті має свої давні традиції. Зародившись у середині ХІХ ст., воно успішно розвивалося в кінці ХІХ ст. – початку ХХ ст. Тут існували різні краєзнавчі товариства: українські, польські та німецькі, які опублікували велику кількість статей на сторінках тогочасних часописів. Іван Франко на це звернув увагу вперше у 1892 р. і узагальнив краєзнавчі досягнення у літературі. «Це перший ступінь, перша прикмета раціональної освіти – знати минуле і сучасне свого народу і відчувати себе живим і свідомим членом живого, свідомого і об’єднаного організму», – писав великий Каменяр у своїй праці «Галицьке краєзнавство». Велике значення для роботи прикарпатських краєзнавців має досвід краєзнавчих товариств минулого, які діяли у Галичині. Їх роботу слід досконало вивчати за архівними і періодичними матеріалами ХІХ – першої половини ХХ ст. Таким чином, важливою науковою проблемою є вивчення в органічному поєднанні наукової і громадсько-культурної діяльності видатного українського історика, археолога, громадського діяча І. Шараневича. Своєю невтомною, наполегливою працею він вніс чималий доробок у вітчизняну історичну науку, зокрема археологію, музеєзнавство, генеалогію та історичну географію. З його громадською діяльністю певною мірою пов’язаний цілий етап політичного і національно-культурного руху в Галичині у другій половині XIX ст. Історична спадщина професора І. Шараневича стала здобутком української історіографії. Він був автором 125 наукових праць, з яких 45 написані польською і німецькою мовами. Його науковий метод служить гідним зразком для нинішніх поколінь істориків, усі наукові праці написано ним на основі першоджерел. Будучи родом із Прикарпаття, він багато зробив для вивчення давньої сторінки історії рідного краю. Незаслужено забутим, фактично забороненим було вивчення діяльності науковця у радянській історіографії. А шкода, бо незаперечним є його значний вклад у розвиток джерелознавства, археології, пам’яткознавства та музеєзнавства не тільки Галичини, але й всієї України. The article is dedicated to one of the famous historians and cultural and political figures of the 19th century – Isidor Ivanovich Sharanevich. The purpose of the research is to analyze the achievements of I. Sharanevich in the field of historical and local history studies on the basis of rich factual material, to highlight the views of the researcher, to reveal his significance in the scientific life of Ukraine at the time, and also to outline the role of I. Sharanevich’s studies in modern historical science. The methodological basis is the principles of objectivity, historicism, scientificity and personification of events. In the process of writing the article, methods of analysis, synthesis, generalization, as well as retrospective, chronological, prosopographic and comparative-historical methods were used. Local history in Prесarpatia has its own ancient traditions. Having originated in the middle of the 19th century, it successfully developed at the end of the 20th century - the beginning of the 20th century. Various local history societies existed here: Ukrainian, Polish and German, which published a large number of articles on the pages of contemporary magazines. Ivan Franko drew attention to this for the first time in 1892 and summarized the achievements of regional studies in literature. «This is the first degree, the first sign of rational education - to know the past and present of one’s people and to feel oneself as a living and conscious member of a living, conscious and united organism,» wrote the great Kamenyar in his work «Galician Local History». The experience of local history societies of the past, which were active in Galicia, is of great importance for the work of Carpathian local historians. Their work should be thoroughly studied based on archival and periodical materials of the 19th and first half of the 20th centuries. Thus, an important scientific problem is the study in an organic combination of the scientific and social and cultural activities of the outstanding Ukrainian historian, archaeologist, public figure I. Sharanevich. With his tireless, persistent work, he contributed a lot to the national historical science, in particular archeology, museology, geneology and historical geography. The entire stage of the political and national-cultural movement in Galicia in the second half of the 19th century is to some extent connected with his social activities. The historical heritage of Professor I. Sharanevich became the achievement of Ukrainian historiography. He was the author of 125 scientific works, of which 45 were written in Polish and German. His scientific method serves as a worthy example for current generations of historians, all scientific works were written by him on the basis of primary sources. Being a native of Prесarpatia, he did a lot to study the ancient history of his native land. The study of the scientist’s activities in Soviet historiography was undeservedly forgotten, actually prohibited. And it’s a pity, because his significant contribution to the development of source studies, archeology, monument studies and museum studies not only in Galicia, but also in the whole of Ukraine is undeniable.